PENGARUH PEMBUATAN KEBUN TOGA TERHADAP PENGETAHUAN DAN SIKAP SISWA SEKOLAH DASAR TENTANG TANAMAN OBAT DI SD INPRES PA'BAENG-BA'BAENG - Amalia, Riska; Syaharullah, Syahradefi; Ameliany, Uphy; Irianti Putri, Windy; Suhasdi, Yudis (Universitas Cokroaminoto Palopo, 2025)
This study aims to examine the impact of creating a Family Medicinal Plants (TOGA) garden on the knowledge and attitudes of elementary school students at Inpres Pa'baeng-Ba'baeng regarding medicinal plants. This research used an experimental design with a pre-test and post-test approach. The students were divided into two groups: an experimental group that directly participated in creating the TOGA garden and a control group that did not participate. Data were collected through quizzes and questionnaires administered before and after the TOGA garden activity. The results showed a significant improvement in students' knowledge and attitudes towards medicinal plants after participating in the TOGA garden activity. The students who participated showed an increased understanding of various types of medicinal plants, their benefits, and demonstrated more concern for utilizing medicinal plants in daily life. This study concludes that creating a TOGA garden can be an effective method for improving students' knowledge and attitudes toward medicinal plants and can encourage the use of medicinal plants in daily life.